Response of the Glutathione (GSH) Antioxidant Defense System to Oxidative Injury in Necrotizing Enterocolitis - Alena Golubkova; Tyler Leiva; Katherine Snyder; Camille Schlegel; Sarah M. Bonvicino; Martin-Paul Agbaga; Richard S. Brush; Jason M. Hansen; Peter F. Vitiello; Catherine J. Hunter (Antioxidants, 2023)
Necrotizing enterocolitis (NEC) is a neonatal intestinal disease associated with oxidative stress. The targets of peroxidation and the role of the innate intestinal epithelial antioxidant defense system are ill-defined. We hypothesized that oxidative stress in NEC correlates with oxidized GSH redox potentials, lipid peroxidation, and a dysfunctional antioxidant system. Methods: Intestinal samples from infants +/− NEC were generated into enteroids and incubated with lipopolysaccharide (LPS) and hypoxia to induce experimental NEC. HPLC assayed GSH redox potentials. Lipid peroxidation was measured by flow cytometry. Immunoblotting measured glutathione peroxidase 4 (Gpx4) expression. Results: GSH redox potentials were more oxidized in NEC intestinal tissue and enteroids as compared to controls. Lipid radicals in NEC-induced enteroids were significantly increased. Human intestinal tissue with active NEC and treated enteroid cultures revealed decreased levels of Gpx4. Conclusions: The ability of neonatal intestine to mitigate radical accumulation plays a role in its capacity to overcome oxidative stress. Accumulation of lipid radicals is confirmed after treatment of enteroids with NEC-triggering stimuli. Decreased Gpx4 diminishes a cell’s ability to effectively neutralize lipid radicals. When lipid peroxidation overwhelms antioxidant machinery, cellular death ensues. Identification of the mechanisms behind GSH-dependent enzyme dysfunction in NEC may provide insights into strategies for reversing radical damage.